2001
DOI: 10.1034/j.1600-0633.2001.100203.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and mortality of prairie stream fishes: relations with fish community and instream habitat characteristics

Abstract: – Few studies have been conducted to describe the age structure, growth rates and mortality of fishes in small stream ecosystems. The purpose of this study was therefore to determine age structure, growth rates and mortality (i.e., total annual mortality and, age‐specific mortality) of central stonerollers Campostoma anomalum, creek chubs Semotilus atromaculatus, red shiners Cyprinella lutrensis and green sunfish Lepomis cyanellus from 13 streams on Fort Riley Military Reservation, Kansas, using incremental gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 43 publications
3
28
0
Order By: Relevance
“…In an Ohio stream with two beaver dams, Storck and Momot (1981) found that a large percentage of the adult creek chub population moved upstream in spring and summer, but typically not more than 300 m. Hall (1972) also found upstream movement in creek chubs in a North Carolina stream and suggested most movements in the studied system were caused by the displacement of reach residents by migrants due to the small number of recaptures in upstream weirs. In a Kansas stream, Quist and Guy (2001) found creek chub total annual survival rate was 28%. However, their samples were dominated by young individuals (\age 2) and survival was over the entire year, whereas our study focused on older individuals ([age 1) during summer and early autumn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an Ohio stream with two beaver dams, Storck and Momot (1981) found that a large percentage of the adult creek chub population moved upstream in spring and summer, but typically not more than 300 m. Hall (1972) also found upstream movement in creek chubs in a North Carolina stream and suggested most movements in the studied system were caused by the displacement of reach residents by migrants due to the small number of recaptures in upstream weirs. In a Kansas stream, Quist and Guy (2001) found creek chub total annual survival rate was 28%. However, their samples were dominated by young individuals (\age 2) and survival was over the entire year, whereas our study focused on older individuals ([age 1) during summer and early autumn.…”
Section: Discussionmentioning
confidence: 99%
“…Creek chubs are typically found around structure (e.g. undercut banks, boulders, root wads), and are mostly insectivores (Taniguchi et al 1998;Quist and Guy 2001). However, creek chubs can become weak to strong piscivores (depending on food availability) as they get larger, typically exceeding 125 mm TL (Schlosser 1988;Jenkins and Burkhead 1994;Pflieger 1997), and can also be cannibalistic (Copes 1978;Fraser and Cerri 1982).…”
Section: Fish Samplingmentioning
confidence: 99%
“…However, a similar study of red shiner provides some basis for comparison. Quist and Guy (2001) found that age-1 red shiners experienced low morality (< 20%), but thereafter mortality rates were in excess of 85% in small Kansas streams. In our study, age-1 sand shiners had much higher mortality (85%) than reported for red shiner but still followed a similar trend of increasing mortality rates among age-2 and older fishes (92%).…”
Section: Data Anafysismentioning
confidence: 99%
“…Mean back-calculated lengths were calculated using the Dahl-Lea method (Summerfelt and Minckley 1969, Quist and Guy 2001, Morey 2004. Total annual mortality was estimated for each reach with a weighted catch curve (Miranda and Bettoli 2007).…”
Section: Data Anafysismentioning
confidence: 99%
“…Both the blackside dace (C. cumberlandensis) and the Tennessee dace (C. tennesseensis) have been shown to use LW as cover (Dolloff and Warren 2003). Other studies have found that creek chub populations are influenced by the presence of woody structures (Quist and Guy 2001). Juvenile creek chub are insectivorous and are able to take advantage of macroinvertebrates that colonize LW, while adult creek chub are general carnivores, feeding opportunistically upon invertebrates and small fishes (Robison and Buchannan 1984).…”
Section: Influence Of Lw On Fish Community Structurementioning
confidence: 99%